The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/4308509
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Location of Virtual Stations in Free-Floating Bike-Sharing Systems with the User Demand during Morning and Evening Rush Hours

Abstract: In recent years, free-floating bike-sharing systems (FFBSSs) have been considerably developed in China. As there is no requirement to construct bike stations, this system can substantially reduce the cost when compared to the traditional bike-sharing systems. However, FFBSSs have also become a critical cause of parking disorder, especially during the morning and evening rush hours. To address this issue, the local governments stipulated that FFBSSs are required to deploy virtual stations near public transit st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
(34 reference statements)
1
14
0
Order By: Relevance
“…The optimization of virtual station locations was addressed in a study of the DBSS of Beijing, China [31]. Although some studies aimed to find virtual stations or zones for new stations, some studies sought to pinpoint exact locations of new stations.…”
Section: Operation Improvement Problemsmentioning
confidence: 99%
“…The optimization of virtual station locations was addressed in a study of the DBSS of Beijing, China [31]. Although some studies aimed to find virtual stations or zones for new stations, some studies sought to pinpoint exact locations of new stations.…”
Section: Operation Improvement Problemsmentioning
confidence: 99%
“…Since the spatial and temporal imbalance between demand (Gervini and Khanal, 2019;Zhou et al, 2018) and (re)distribution (Ho and Szeto, 2017;Li et al, 2016) of sharing bikes is identified as the key to successful SBP development, some researchers have used different repositioning technologies and models to optimize the station position and address congestion or starvation issues of IT-based SBP (Forma et al, 2015;Ghosh et al, 2017;Szeto and Shui, 2018). This is of particular importance for DSBs due to their flexibility without docking stations, so demand forecasting (Xu et al, 2018), static (Liu et al, 2018) and dynamic repositioning problems (Shui and Szeto, 2018), optimizing location (Sun et al, 2019) and optimizing transportation planning (Sayyadi and Awasthi, 2018) are the key focuses of DSBs research as well in the transportation literature.…”
Section: Figmentioning
confidence: 99%
“…These studies may be categorised into three hierarchical levels, including strategic design, tactical development and operations management [9]. In terms of strategic design, research has been aimed to ensure satisfactory levels of service and inventory in bike-sharing networks through rational planning of the location and capacity of the stations and/or parking places, thereby reducing user dissatisfaction, station construction cost, or both, e.g., [10,11,12,13,14,15]. The studies at the tactical level have focused on formulating various user incentive policies in an effort to encourage users to ride shared bikes from oversupplied areas to undersupplied areas, e.g., [16,17,18].…”
Section: Introductionmentioning
confidence: 99%